Hundreds of Afghan soldiers to become eligible to live in UK after new information found - Sabbagh, Dan (The Guardian, 2024)
Estimated 500 rejected cases expected to be overturned after fresh evidence they were employed by the UK government in Afghanistan.
Keywords: Afghanistan; Immigration and asylum; Military; UK news; World news